Comparison of tomato root distributions by minirhizotron and destructive sampling - Machado, Rui (2003)
Abstract Calibration of minirhizotron data against root length density (RLD) was carried out in a field trial where three drip irrigation depths: surface (R0) and subsurface, 0.20 m (RI) and 0.40 m depth (RII) and two processing tomato cultivars: `Brigade' (CI) and `H3044' (CII) were imposed. For each treatment three minirhizotron tubes were located at 10, 37.5 and 75 cm of the way from one plant row to the next. Roots intersecting the minirizotrons walls were expressed as root length intensity (L a) and number of roots per unit of minirhizotron wall area (N ra). Root length density (RLD) was calculated from core samples taken for each minirhizotron tube at two locations: near the top of the minirhizotron (BI) and 15 cm apart from it, facing the minirhizotron wall opposite the plant row (BII). Minirhizotron data were regressed against RLD obtained at BI and BII and with their respective means. The results show that for all the situations studied, better correlations were obtained when RLD was regressed with L a than with N ra. Also was evident that the relationship between L a and RLD was strongly influenced by the location of soil coring. RLD was correlated with L a trough linear and cubic equations, having the last ones higher determination coefficients. For instance at 10 cm from the plant row when values from the top layer (0–40 cm) were analysed separately, L a was significantly regressed with RLD measured at BII and described by the equations: RLD = 0.5448 + 0.0071 L a (R 2 = 0.51) and RLD = 0.4823 + 0.0074L a + 8×10–5 L a 2 – 5×10–7 L a 3 (R 2 = 0.61). Under the 40 cm depth the highest coefficients of determination for the linear and cubic equations were respectively 0.47 and 0.88, found when L a was regressed with RLD measured at BI. For minirhizotrons located at 75 cm from the plant row and for location BI it was possible to analyse jointly data from all depths with coefficients of determination of 0.45 and 0.59 for the linear and cubic equations respectively.